Analisis Pengaruh Rasio Likuiditas, Rasio Solvabilitas, dan Efisiensi Operasi Terhadap Kinerja Keuangan (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2019-2023): Analysis of the Impact of Liquidity Ratios, Solvency Ratios, and Operational Efficiency on Financial Performance (A Study of Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2019–2023) - Carolina Marisi Mora Nainggolan (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to understand how these factors can provide a comprehensive picture of the stability and effectiveness of financial management in the manufacturing sector which has an important role in the national economy. This study uses a descriptive quantitative method, research data in the form of annual financial statements from 10 selected manufacturing companies using purposive sampling techniques. The analysis was carried out through the panel data regression method, and with classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure the validity of the regression model. This study uses indicators such as current ratio (Liquidity Ratio), debt to equity ratio (Solvency Ratio), total asset turnover (Operating Efficiency), and return on asset (Financial Performance). The results of the study show that in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period, the Liquidity Ratio, Solvency Ratio, and Operating Efficiency partially have a significant effect on Financial Performance. This is shown by the p-values of 0.025, 0.033, and 0.015, respectively, which are smaller than the alpha 0.05. Simultaneously, the F-calculation test of 8.362 with a p-value of 0.015 also confirms that the three independent variables together have a significant influence on the company's Financial Performance